KEMAMPUAN CAMAT DALAM PENYELENGGARAAN TUGAS UMUM PEMERINTAHAN BERDASARKAN PP NO.19 TAHUN 2008 TENTANG KECAMATAN DI KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA - Ririn Wahyuningsih E42009076 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
AbstractA Research of The Application of Based Leadership district head PP No.19 of 2008 About districtsRasau Jaya district in Kubu Raya Regency. This essay aims to identify and analyze the districtleadership in carrying out their duties and obligations to govern under Regulation No.19 of 2008 onSub Rasau Jaya district in Kubu Raya Regency. This study uses a descriptive type of research with aqualitative approach. The research result showed that there are limitations on the authorityleadership since the occurrence of a PP No.19 of 2008 concerning districts can be seen from thesame leadership Auth with the job at hand at other SKPD and leadership job as coordinatororganizers only rule in chapter 15 on the PP.Keywords: Leadership, Authority, the Applicable Regulations.